Rate-compatible distributed arithmetic coding - Grangetto, M.; Magli, E.; Tron, R.; Olmo, G. (IEEE communications letters, 2008)
Distributed arithmetic coding has been shown to be effective for Slepian-Wolf coding with side information. In this letter, we extend it to rate-compatible coding, which is useful in presence of a feedback channel between encoder and decoder. The performance loss with respect to the original version is negligible.